Increased expression of fibroblast growth factor 13 in prostate cancer is associated with shortened time to biochemical recurrence after radical prostatectomy. Issue 1 (12th March 2016) - Yu, Lan; Toriseva, Mervi; Tuomala, Miikka; Seikkula, Heikki; Elo, Teresa; Tuomela, Johanna; Kallajoki, Markku; Mirtti, Tuomas; Taimen, Pekka; Boström, Peter J.; Alanen, Kalle; Nurmi, Martti; et al.
Abstract : Fibroblast growth factor homologous factors (FHFs) belong to the fibroblast growth factor (FGF) superfamily, which plays an important role in prostate cancer (PCa). Mining of public database suggests that FGF13 (FHF2) mRNA expression is altered in over 30% of PCa cases. This study examined the FGF13 expression pattern in human PCa specimens and evaluated its potential as a biomarker for patient outcome after radical prostatectomy (RP). Immunohistochemistry (IHC) showed that FGF13 was detectable in the majority of human PCa samples, and FGF13 IHC scores were higher in high‐grade prostatic intraepithelial neoplasia, in primary PCa and in metastatic PCa than in benign prostatic tissue. There was a significant association between high cytoplasmic FGF13 staining and a risk of biochemical recurrence (BCR) after RP. This was also evident in the intermediate to high‐risk patient groups. In contrast, positive nuclear FGF13 staining along with low cytoplasmic FGF13 group showed a decreased BCR risk. Multivariate regression analysis indicated that high cytoplasmic FGF13 staining was associated with BCR and that this could serve as an independent prognostic marker in PCa. Several PCa cell lines showed increased FGF13 expression at the mRNA and protein levels compared to the immortalized prostate epithelial cell line PNT1a. Analysis of co‐labeled cells suggested a possible interaction of FGF13 with α‐tubulin and the voltage‐gated sodium channel proteins (NaV s/VGSCs). Our data indicate that, for PCa patients after RP, FGF13 serves as a potential novel prognostic marker that improves prediction of BCR‐free survival, in particular if combined with other clinical parameters. Abstract : What's new? Although localized prostate cancer can be treated by radical prostatectomy, some operated patients progress to incurable disease despite surgery. Hence, the discovery of novel biomarkers could enable the identification of patients who are at risk of disease progression, potentially improving outcomes. Promising markers may exist in fibroblast growth factor (FGF) signaling pathways, which are important in prostate cancer regulation. Here, disturbed expression of FGF13 was identified in a majority of human prostate cancer specimens. Elevated cytoplasmic FGF13 expression was associated with biochemical recurrence following radical prostatectomy. FGF13 could be a novel prognostic marker in prostate cancer.